Antibacterial activity of Aleurites moluccana against some clinical isolates of gram-positive and gram-negative bacteria - Abd. Samah, Othman; Mohamad Razar, Rasyidah (BioTek Journal, India, 2009)
Aleurites moluccana extracts were found to inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa in a previous study.11 The antibacterial activities of acetonitrile, methanol and water extracts of husk, leaf and stem bark of A. moluccana were further investigated against 8 clinical isolates. The disc diffusion assays showed that crude extract of A. moluccana inhibited the growth of Staphylococcus aureus (S 277), Streptococcus pyogenes (S 526), Pseudomonas aeruginosa (P 84) and Klebsiella pneumoniae (K 6). The lowest MIC for P. aeruginosa (P 84) was exhibited by methanol extract of stem bark at concentration 98 µg/ml and S. pyogenes (S 526) at 781 µg/ml whilst both S. aureus (S 277) and K. pneumoniae (K 6) exhibited in acetonitrile of husk at 195 µg/ml and 6.25 µg/ml, respectively. The antibacterial action was bactericidal for all bacteria except for S. pyogenes (S 526) where the action was bacteriostatic. The highest polyphenols content was observed in methanol extract of stem bark. The overall results indicate that the extracts from the stem bark are potential source of phytomedicine agents for both Gram-positive and Gram-negative bacteria.